Pulmonary Surfactant Treatment for Preterm Infants With Respiratory Distress Syndrome: A Nationwide Survey - Haifeng Zong; Chuanzhong Yang; Long Chen; Yong Ji; Rong Ju; Jiangqin Liu; Ling Liu; Jingyun Shi; Hui Wu; Lili Wang; Falin Xu; Huayan Zhang; et al. (The Clinical Respiratory Journal, 2026)
ABSTRACT Background Pulmonary surfactant is essential for neonatal respiratory distress syndrome (RDS) management, yet national data on how surfactant is used in China are limited. We surveyed current practices and variation in surfactant availability and administration. Methods In October–December 2022, a nationwide cross‐sectional online survey was completed by one neonatologist from each of 394 hospitals across 30 provinces. Items covered surfactant availability (including delivery room access), product selection, dosing, timing, and administration techniques. Results Surfactant was available in 96.7% of hospitals; poractant alfa and calsurf were available in 88.6% and 58.1%, respectively. Only 51.6% of hospitals reported surfactant availability in delivery rooms. For the first dose, 200 mg/kg was preferred for poractant alfa (68.8%) and 100 mg/kg for calsurf (63.8%). The reported median time to first dose was 2.0 h after birth; poractant alfa was administered sooner than calsurf (10 vs. 30 min estimated administration time; p < 0.001). Most respondents (79.7%) reported giving surfactant after noninvasive ventilation failure in infants who subsequently required mechanical ventilation, with higher use in tertiary vs. secondary hospitals (82.1% vs. 71.7%; p = 0.03). Intubation‐surfactant‐extubation (INSURE) and less invasive surfactant administration (LISA)/minimally invasive surfactant therapy (MIST) were available in 86.5% and 49.7% of hospitals, respectively. Additionally, 25.1% of the respondents reported combining a surfactant with glucocorticoids for treating RDS. Conclusion Surfactant use in China shows substantial between‐hospital variation, particularly in delivery room access and less invasive administration. Standardized training and improved resource allocation may reduce disparities and support timely, evidence‐based surfactant therapy.